A Case Study On Evaluation Of ICEMS System At Multimedia University - Abdalla Mohammed, Aymen Gafar (2005)
In this study, an evaluation for online system platform ICEMS was formed to enable and help university teachers and administrators to adopted with the educational administration, supervision, planning and economic. In addition strategic analysis and applications of the ICEMS were discussed.